2011
DOI: 10.1111/j.1541-4337.2011.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Content and Methods for Cholesterol Determination in Meat and Poultry

Abstract: Available data for cholesterol content of beef, pork, poultry, and processed meat products were reported. Although the cholesterol concentration in meat and poultry can be influenced by various factors, effects of animal species, muscle fiber type, and muscle fat content are focused on in this review. Oxidative red muscles tend to have greater total lipid and cholesterol contents, although differences in the same types of muscles or cuts have been reported. Moreover, contradictory results among various studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 228 publications
(798 reference statements)
5
65
1
1
Order By: Relevance
“…According to Surai and Sparks (2000), the proportion of n-3 PUFA in different chicken tissues was higher when the diet was supplemented with vitamin E. Other authors (Cortinas et al, 2004;Rymer and Givens, 2010) found no effect of supplementing broiler diets with vitamin E on the fatty acid profile of thigh and breast meat. In the current study, in birds fed rape seeds and fish oil the cholesterol content in breast and thigh meat was 65.8 and 84 mg · 100 g ) given by Ajuyah et al (1991), slightly lower than presented by Grau et al (2001), and within the limits reported for broiler meat in the review by Dinh et al (2011). The dietary level of vitamin E and Se affected neither cholesterol nor 25-OH-cholesterol contents in meat after 3 months frozen storage.…”
Section: Discussionmentioning
confidence: 78%
“…According to Surai and Sparks (2000), the proportion of n-3 PUFA in different chicken tissues was higher when the diet was supplemented with vitamin E. Other authors (Cortinas et al, 2004;Rymer and Givens, 2010) found no effect of supplementing broiler diets with vitamin E on the fatty acid profile of thigh and breast meat. In the current study, in birds fed rape seeds and fish oil the cholesterol content in breast and thigh meat was 65.8 and 84 mg · 100 g ) given by Ajuyah et al (1991), slightly lower than presented by Grau et al (2001), and within the limits reported for broiler meat in the review by Dinh et al (2011). The dietary level of vitamin E and Se affected neither cholesterol nor 25-OH-cholesterol contents in meat after 3 months frozen storage.…”
Section: Discussionmentioning
confidence: 78%
“…In human nutrition, attention is paid to the amount of cholesterol, the daily consumption of which should be about 300 mg (Chizzolini et al, 1999;Dinh et al, 2011). Abdominal fat from geese is more favourable than subcutaneous fat due to its lower cholesterol content (Pikuł, 1996).…”
Section: Physicochemical Fat Propertiesmentioning
confidence: 99%
“…Fat, protein, moisture, iron, kalium, calcium and phosphorus were determined by the method of AOAC (2012), whereas cholesterol was determined by the method as described by Dinh et al (2008Dinh et al ( , 2011. Amino acid composition was measured by the method as described by Henderson and Brooks (2010), and fatty acid composition was determined by the method as described by Almeida et al (2006).…”
Section: Sampling and Laboratory Analysismentioning
confidence: 99%